2017
DOI: 10.1111/fare.12292
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance Versus Support: Perceptions of Residential Community Climate Among LGB Parents

Abstract: LGB parents' perceptions of climate reveal specific community features that need to be strengthened to promote family well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…This study also revealed that support mechanisms available through gay parenting groups provide crucial resources for queer families, adding to findings from Oswald, Routon, McGuire, and Holman (2018) on the importance of personal and social supports within the context of positive community climates for providing a sense of being supported. This was especially true for gay fathers who had children via heterosexual unions and who were facing immediate crises of family disillusionment, depression, and disconnection from their communities of origin.…”
Section: Discussionsupporting
confidence: 52%
“…This study also revealed that support mechanisms available through gay parenting groups provide crucial resources for queer families, adding to findings from Oswald, Routon, McGuire, and Holman (2018) on the importance of personal and social supports within the context of positive community climates for providing a sense of being supported. This was especially true for gay fathers who had children via heterosexual unions and who were facing immediate crises of family disillusionment, depression, and disconnection from their communities of origin.…”
Section: Discussionsupporting
confidence: 52%
“…Perhaps most notably, research in the past decade highlights the unique role of social stigma and social support in SGM parenting dynamics. Supportive social and legal communities significantly improve experiences of social stigma, depression, and anxiety (Bos, Knox, van Rijn‐van Gelderen, & Gartrell, ; Goldberg & Smith, ; Oswald, Routon, McGuire, & Holman, ). Although one study of 92 adoptive families reports that parents in same‐sex and different‐sex couples have similar amounts of social support from network members (Sumontha, Farr, & Patterson, ), most other research shows that sexual‐minority parents experience high social stigma and less social support than their heterosexual counterparts.…”
Section: Sexual‐ and Gender‐minority Parenthoodmentioning
confidence: 99%
“…Queer theory places sexuality at the center of analysis through which social, political, and cultural phenomena are examined (Edgar & Sedgwick, ). Queer theory connects the personal, or identity, to local (Acosta, ; Fish & Russell, 2018; Oswald, Routon, McGuire, & Holman, ) and larger sociopolitical and institutional contexts (e.g., Widiss, ). Queer theory interrogates the privileged statuses of traditional constructions of sex, gender, femininity, masculinity, heteronormativity, and heteropatriarchy (e.g., Jagose, ).…”
Section: Situating the Critical Theoretical Terrain Of Gender Feminimentioning
confidence: 99%